Judicial Transformation During Omar bin Abdul Aziz's Period (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2017)
The renewal carried out by Umar bin Abdul Aziz in the judiciary is the Mazhalim court, whose object is the rulers, his family and himself. In this way the Mazhalim court initiated by Abdul Malik Bin Marwan has been very effective. Umar bin Abdul Aziz said "the implementation of hudud is the same as the implementation of other Shari'ah without exception but when it comes to eliminating the life of someone Umar bin Abdul Aziz ordered the Governors of all regions to seek his approval first.       The corruption trial was carried out by Umar bin Abdul Aziz in the practice of uniq and ijtihad especially. The act of corruption perpetrated by Yazid ibn Muhallab is not considered a thief because the treasure taken is the right of the people who are also his ( شبَ الو لك ) then Yazid bin Muhalab's hand is not cut but imprisoned until he can return the treasure he embezzled. In the court of Hisbah Umar bin Abdul Aziz has given the limits for animals such as donkeys and camels, which should not exceed 600 Ritl (272,15542 Kg). Umar bin Abdul Azizialso provided funds from the Baitul Mal for the marriage of married youths who were announced in the ceremony as in the market to foster morality of Muslims.